2018
DOI: 10.1371/journal.pone.0204095
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of strain elastography, point shear wave elastography using acoustic radiation force impulse imaging and 2D-shear wave elastography for the differentiation of thyroid nodules

Abstract: PurposeThe aim of the study was to compare three different elastography methods, namely Strain Elastography (SE), Point Shear-Wave Elastography (pSWE) using Acoustic Radiation Force Impulse (ARFI)-Imaging and 2D-Shear Wave Elastography (2D-SWE), in the same study population for the differentiation of thyroid nodules.Materials and methodsAll patients received a conventional ultrasound scan, SE and 2D-SWE, and all patients except for two received ARFI-Imaging. Cytology/histology of thyroid nodules was used as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 44 publications
(57 reference statements)
0
20
0
3
Order By: Relevance
“…Our analysis showed that the pooled sensitivity (88%) and specificity (91%) of SWE in detecting and staging early cirrhosis (F1) are similar to those of TE [37,48], acoustic radiation force impulse (ARFI) [49] and RTE [50,51], those sensitivity and specificity are 83 and 89%, 87 and 87%, 74 and 84%, respectively. ARFI is very similar to SWE, which targets an anatomic region to be interrogated for elastic properties with a Region-of-Interest (ROI) cursor [52]. However, for significant fibrosis (F ≥ 2), the overall sensitivity and specificity of SWE are greater than these of TE and RTE, and similar to these of ARF.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis showed that the pooled sensitivity (88%) and specificity (91%) of SWE in detecting and staging early cirrhosis (F1) are similar to those of TE [37,48], acoustic radiation force impulse (ARFI) [49] and RTE [50,51], those sensitivity and specificity are 83 and 89%, 87 and 87%, 74 and 84%, respectively. ARFI is very similar to SWE, which targets an anatomic region to be interrogated for elastic properties with a Region-of-Interest (ROI) cursor [52]. However, for significant fibrosis (F ≥ 2), the overall sensitivity and specificity of SWE are greater than these of TE and RTE, and similar to these of ARF.…”
Section: Discussionmentioning
confidence: 99%
“…Though the SR is a semiquantitative method, it is defined as the ratio obtained by dividing the mean strain within the lesion by the mean strain of the surrounding normal tissue; thus, thyroid echogenicity surrounding thyroid nodules will inevitably affect the SR. As a result, it might be inferred that no additional information is provided by the SR, which is more time consuming than the ES, in the discrimination of malignant from benign thyroid nodules. Although shear wave elastography (SWE) has drawn more attention in recent years and has been reported to be more accurate than USE in some studies [30][31][32], Tian et al's and Hu et al's meta-analysis showed that USE had a better diagnostic performance than SWE, with comparable specificity between methods [33,34]. Even more recently, a prospective study comprising 243 nodules revealed that USE yielded the highest performance compared with the TI-RADS score and SWE [35].…”
Section: Discussionmentioning
confidence: 99%
“…Dabei wird die Ausbreitungsgeschwindigkeit je nach Verfahren entweder in m/s angegeben oder die Steifheit durch eine Formel aus Gewebedichte und Ausbreitungsgeschwindigkeit berechnet und in kPa angegeben. Der direkte Vergleich unterschiedlicher Elastographiemethoden zeigt für alle Verfahren eine sehr gute Anwendbarkeit, möglicherweise mit geringen, im Alltag mutmaßlich nicht relevanten Vorteilen für die Shear-Wave Verfahren [36].…”
Section: Elastografie Der Schilddrüse - Rationale Und Methodenunclassified